Rhythm perception and production predict reading abilities in developmental dyslexia - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Zoia, Stefania; Buda, Sonia; Tilli, Sara; Monasta, Lorenzo; Montico, Marcella; Sila, Alessandra; Ronfani, Luca; Schön, Daniele (Frontiers in Human Neuroscience, 2014)
Rhythm organizes events in time and plays a major role in music, but also in the phonology and prosody of a language. Interestingly, children with developmental dyslexia - a learning disability that affects reading acquisition despite normal intelligence and adequate education - have a poor rhythmic perception. It has been suggested that an accurate perception of rhythmical/metrical structure, that requires accurate perception of rise time, may be critical for phonological development and subsequent literacy. This hypothesis is mostly based on results showing a high degree of correlation between phonological awareness and metrical skills, using a very specific metrical task. We present new findings from the analysis of a sample of 48 children with a diagnosis of dyslexia, without comorbidities. These children were assessed with neuropsychological tests, as well as specifically-devised psychoacoustic and musical tasks mostly testing temporal abilities. Associations were tested by multivariate analyses including data mining strategies, correlations and most importantly logistic regressions to understand to what extent the different auditory and musical skills can be a robust predictor of reading and phonological skills. Results show a strong link between several temporal skills and phonological and reading abilities. These findings are discussed in the framework of the neuroscience literature comparing music and language processing, with a particular interest in the links between rhythm processing in music and language.